Supporting Teachers’ Professional Development: Examining the Opinions of Pre-school Teachers Attending Courses in an Undergraduate Program - TORAN, MEHMET; YAĞAN, SEVCAN (Pegem Akademi Yayıncılık, 2020)
This study aimed to determine the opinions of preschool teachers about courses they attended in a preschool undergraduate program in order to support their professional development. The case study, one of the qualitative research designs, was adopted in the study. Two sampling strategies, snowball and criterion sampling, were used for the determination of participants. 26 teachers from 6 different preschools voluntarily participated in the research. The data were collected through semi-structured interviews carried out in two steps; before and after participating in the courses in the preschool undergraduate program. Descriptive analysis was employed in the analysis of the data. Results revealed that preschool teachers put into practice in-service program outputs tailored to their needs and in line with their professional development needs and made suggestions so that in-service training programs to be designed for their professional development can be more effective. In conclusion, the preschool teachers were found to need alternative in-service training programs.
Keywords: In-service Training; Professional Development; Preschool Teacher; Preschool Education